The conical Radon transform with vertices on triple line segments. (23rd October 2020) - Moon, Sunghwan; Haltmeier, Markus
Abstract: We study the inversion of the conical Radon transform which integrates a function on the surface of a cone. The conical Radon transform recently got significant attention due to its relevance in various imaging applications such as Compton camera imaging and single scattering optical tomography. The unrestricted conical Radon transform is over-determined because the manifold of all cones depends on six variables: the center position, the axis orientation and the opening angle of the cone. In this work, we consider a particular restricted conical Radon transform using triple linear sensor of finite length where integrals over a three-dimensional set of cones are collected, determined by a one-dimensional vertex set, a one-dimensional set of central axes, and a one-dimensional set of opening angle. As the main result in this paper we derive an analytic inversion formula for the restricted conical Radon transform. Along that way we define a certain ray transform adapted to the triple line sensor for which we establish an analytic inversion formula.